ANALISIS USAHA DAN PRODUKTIVITAS USAHA PENGOLAHAN AMPLANG IKAN PIPIH (Notopterus chilata) DI KOTA SAMARINDA (STUDI KASUS PADA UD. AMPLANG JUANDA) - Dedi Saputra Wardana; Said Abdusysyahid; Heru Susilo (Jurnal Pembangunan Perikanan dan Agribisnis, 2016)
The aims of this study are, knowing the knife fish processing activities at Amplang Juanda, measuring the economic performance of business through profits, payback period (PP), break evenpoint (BEP), revenue cost ratio (RCR), and to know the marketing channels of the knife fish amplang on the business Amplang Juanda. The results showed that amplang knife fish processing business run by Amplang Juanda is profitable, evidenced by the profit value of IDR 2.259.425 per month, revenue cost ratio of 1,34 (RCR>1), the actual condition of production and the price is above break evenpoint condition, payback period for 1,9 months. Marketing channel amplang knife fish that occur are zero-level marketing channel. Labor productivity by an average of 9 packs/hour. Every hour their labor can produce amplang 9 packs/hour or 2,7 kg/hour. Fish productivity of 0,96 kg of amplang per 1 kg of fish. Every 1 kg of knife fish can produce as much as 0,96 kg amplang knife fish.